STATE POLICY PRIORITIES FOR STIMULATING THE DEVELOPMENT OF THE HOUSING STOCK OF UKRAINE: THE ASPECT OF INVESTMENT ACTIVITY - ZABASHTANSKYI, Maksym; ROGOVYI, Andrii (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article substantiates the need to implement the state policy of stimulating the development of the housing stock of Ukraine. Until now, Ukraine has implemented a significant number of measures to create, and then improve, regulatory and legal support for investment activities in the housing market. Obstacles and problems in the field of housing construction that prevent the formation and realization of its investment potential and provision are emphasized. To date, while implementing its state policy of stimulating the development of the housing stock, Ukraine has not been able to create a favorable and sufficiently competitive investment environment. The biggest problem today is the lack of control over the implementation of investment legislation, which would be applied to protect the rights and legitimate interests of Ukrainian enterprises, including in the housing construction sector. One of the most significant problems that emerges from year to year is the low level of investments in the residential construction sector of Ukraine. The priorities of the state policy of stimulating the development of the housing stock of Ukraine, taking into account the aspects of investment activity, include creating a favorable investment environment, increasing the volume of capital investments, improving the structure of investments, ensuring a high level of protection of the interests and rights of investors, increasing the efficiency of the use of investments and the investment process, developing cooperation in the field of investment - innovative activity. In the context of state policy priorities, actual means of achieving them are defined. We consider the main problem of the state policy of stimulating the development of the housing stock to be the impossibility of state authorities to coordinate the theoretical and practical parts of the implementation of all necessary actions and measures. Therefore, in addition to state regulatory bodies, the main implementers of this state policy should include the legislative branch of government and local authorities.